ANALYSIS OF CHARACTER EDUCATION MODELS TO PREVENT BULLYING AMONG PRIMARY SCHOOL STUDENTS - Fitriani, Aulia; Zahra, Indah Sapira; Farhurohman, Oman (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2026)
The phenomenon of bullying in primary schools continues to be a serious problem that threatens the psychological, social, and academic development of students. Data shows that Indonesia has a high rate of bullying, with primary schools contributing significantly to cases of violence in the educational environment. This condition highlights the urgency of reviewing character education models as a systematic and sustainable preventive approach. This study aims to analyse effective character education models in preventing bullying among primary school students through a Systematic Literature Review (SLR) approach. The literature selection process was conducted using the PRISMA protocol by searching for scientific articles through Google Scholar indexed by SINTA, published between 2017 and 2025, and focusing on the Indonesian educational context. From the results of the gradual selection, ten articles that met the inclusion criteria were obtained and analysed using content analysis techniques. The results of the study show that effective character building models include instilling values, teacher role modelling, integrating character into the curriculum and extracurricular activities, and active collaboration between schools, families, and communities. Bullying in primary schools is multifactorial, with family factors, parenting patterns, and teacher consistency as the main determining variables. The conclusion of this study confirms that a holistic, structured character approach involving all stakeholders is the most optimal strategy for creating a safe, inclusive school ecosystem that is free from all forms of bullying.